Development of an Automated Mushroom House to Optimize Growth and Production of White Oyster Mushrooms (Pleurotus ostreatus) - Baharsyah, Nur Intan; Jamaluddin, Jamaluddin; Mukhlis, Andi Muhammad Akram (Journal of Agroscience Indonesia, 2023)
Oyster mushroom cultivation is usually done in the highlands which have very low temperatures, while in the lowlands it is cultivated in mushroom houses that have set the temperature and humidity. The manufacture of mushroom houses in this study can regulate temperature and humidity automatically with physical conditions that are in accordance with oyster mushroom cultivation, so that this system can be implemented in mushroom farmers. This research aims to make a prototype and measure the performance of an automatic-based white oyster mushroom house (pleurotus ostreatus). To fulfill the design, the tool manufacturing process is carried out. The procedure for making tools is carried out through stages, consisting of: preparation of tools and materials, design procedures, making design drawings, namely structural and functional designs and the last is product testing. Based on the results of the tool testing, a description of the functional test results using the DHT22 sensor calibration with a hygrometer measuring instrument, obtained a percentage error of 1.58% and an average humidity of 14.08%. Thus, all components of the tool used can function properly such as water pumps, microcontrollers, mini ac and LCD. While the results of field testing show that the average mushroom growth is 7 cm and 8 cm in diameter for 3 weeks. These results indicate that the growth of oyster mushrooms in mushroom houses grows well.